2002
DOI: 10.1897/1551-5028(2002)021<2606:ioaowt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Onsite Wastewater Treatment System in Sandy Soil: Site Characterization and Fate of Anionic and Nonionic Surfactants

Abstract: This study reports on the fate of linear alkylbenzene sulfonate (LAS), alcohol ethoxylate (AE), and alcohol ether sulfate (AES) surfactants in a home septic system near Jacksonville (FL, USA) that has been used since 1976. The drainfield at this site resides in fine sand (< 6% silt and clay) with an unsaturated zone that ranges from 0 to 1.3 m. During the wettest times of the year, it is likely that effluent from the septic system passes directly into the groundwater without exposure to an unsaturated zone of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…This study was part of a program that investigated the fate and transport of household cleaning product surfactants in onsite wastewater treatment systems (OWTS) [1,2]. Sorption and biodegradability characteristics are two important parameters for determining the fate of a material in the soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a program that investigated the fate and transport of household cleaning product surfactants in onsite wastewater treatment systems (OWTS) [1,2]. Sorption and biodegradability characteristics are two important parameters for determining the fate of a material in the soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed characterization of the surficial geology at the study site can be found in Nielsen et al [6]. Briefly, the soils are characterized as Adamsville fine sand.…”
Section: Site Characteristicsmentioning
confidence: 99%
“…The surfactants investigated (LAS, AES, and AE) were all measured in the STE and saturated zone discharge plume during November 1993 and May 1995 [6]. These determinations were used to test the predictability of the model.…”
Section: Field Monitoringmentioning
confidence: 99%
See 2 more Smart Citations